The rise of thrift entrepreneurs reveals emerging business opportunities in a circular fashion through sustainable, resale-driven practices - Egbere Michael Ikechukwu; Tijjani Ahmed Ajayi; Dr. Sneha Chaurasiya; Shiva Raj Ghimire; B.M. Sajedul Karim; Asma Khan; Yasotha Nair Tramankuti (Journal of Commerce, Management, and Tourism Studies, 2026)
This study investigates the role of thrift entrepreneurs in the emerging circular economy, examining how they use digital platforms to promote sustainable consumption and navigate systemic barriers in informal market environments. It explores the socio-cultural, technological, and institutional factors that enable or constrain their participation in circular fashion ecosystems. Using a qualitative research design, the study employs document analysis, thematic coding, and a secondary literature review, drawing on recent empirical data from Southeast Asian digital thrift markets. The analysis is framed by Digital Inequality Theory (Robinson et al., 2015), Social Capital Theory (Putnam, 2000), and circular economy frameworks (OECD, 2022). Findings reveal six core themes: circular values and sustainability narratives; digital adaptation and entrepreneurial bricolage; informality, inequity, and exclusion from formal capital and regulation; social capital formation and cultural community-building; identity politics in thrift branding; and the need for nuanced, inclusive policy responses. The study concludes that equitable circular economies require robust policy frameworks, improved digital infrastructure, and formal recognition of informal entrepreneurial actors, and calls for future interdisciplinary research.